Pubic osteomyelitis after surgery for perforated colonic diverticulitis with fecal peritonitis: A case report. (2017) - Kitaguchi, Daichi; Enomoto, Tsuyoshi; Ohara, Yusuke; Oda, Tatsuya; Ohkohchi, Nobuhiro
Highlights: An early diagnosis of pubic osteomyelitis is difficult to obtain because the symptoms are nonspecific and do not present the typical septic arthritis of a joint. Delayed diagnosis and treatment leads to progressive bone degradation and induces severe complications, resulting in severe pelvic pain and a wide-based gait. A definitive diagnosis by CT and MRI and appropriate antimicrobial therapy combined with surgical treatment are important for pubic osteomyelitis. Abstract: Introduction: Pubic osteomyelitis is a rare type of suppurative osteomyelitis. Early diagnosis of pubic osteomyelitis is difficult, and prolonged inflammation results in progressive bone degradation, severe pelvic pain and a wide-based gait. Presentation of case: We report the case of an 82-year-old woman who was admitted to a previous hospital with severe abdominal pain caused by a perforated colonic diverticulum with fecal peritonitis. She underwent an emergency operation and a postoperative wound infection occurred. Despite treatment of the infection, purulent exudate was discharged for three months and she gradually showed a gait disturbance. CT and MRI revealed that pubic symphysis showed osteolysis and there was severe inflammation around the wound. After administration of appropriate antibiotics, an operation, which included the removal of a fistula, debridement of sequestra and lavage of the abscess cavity, was performed. The inflammation improved promptly after the operation, and the patient was discharged on postoperative day 27 without any complications. Discussion: Pubic osteomyelitis does not show the findings of typical acute suppurative osteomyelitis and hematological findings are nonspecific. It is important for early diagnosis to consider the risk factors of pubic osteomyelitis during examination. Conclusion: We would emphasize that a definitive diagnosis by CT and MRI and appropriate antimicrobial therapy combined with surgical treatment are important for pubic osteomyelitis.